Welfare-to-work programme: woman participants' perceptions of how the programme in Johannesburg impacted on their livelihoods - Radebe, Tani (My University, 2018)
The number of young women who are in receipt of Child Support Grants is increasing every year. Acknowledging that the issuing of Child Support Grants does not promote self-reliance, the Gauteng Department of Social Development adopted Welfare-to-Work Programme as an exit strategy for recipients of Child Support Grant. The programme aimed to capacitate the recipients of Child Support Grant with skills and knowledge that could enable them to secure jobs. The purpose of the study was to explore participants’ perceptions and experiences of how the programme impacted on their livelihoods. A qualitative research method, namely a case study, was utilized to conduct the research. The purposive sampling was chosen to select nine participants, namely young women who were in receipt of Child Support Grants and who completed the said programme in Johannesburg region. Semi-structured interviews were utilized to collect data and thematic analysis was utilized to analyze data. The main findings of the research were that the boot camp section of the programme had a significant impact on the participants’ lives; it was experienced as therapeutic and uplifting. Through the boot camp the participants managed to develop the self-awareness and self-understanding. However, the main objective of the programme which was to remove participants from welfare to work was not achieved. Participants remained in the welfare system when the programme ended. It is recommended the implementers of the programme do a thorough assessment of the skills required by participants to secure stable employment in their communities. The programme should be monitored and evaluated on an ongoing basis in order to make necessary adjustments to facilitate participants securing suitable employment when completing the programme.
University of the witwatersrand,Johannesburg School of Human and Community Development School of Social work Research Report submitted to the faculty of humanities in partial fulfilment of Master of Arts(MA) in Social Development, 2018
Keywords: Poverty--Government policy; Social service; Grants-in-aid--South Africa